Second order nonlinear frequency generation at the nanoscale in dielectric platforms. Issue 1 (31st December 2022) - Rocco, Davide; Morales, Rocio Camacho; Xu, Lei; Zilli, Attilio; Vinel, Vincent; Finazzi, Marco; Celebrano, Michele; Leo, Giuseppe; Rahmani, Mohsen; Jagadish, Chennupati; Tan, Hoe; Neshev, Dragomir; et al.
ABSTRACT: Nonlinear frequency generation at the nanoscale is a hot research topic which is gaining increasing attention in nanophotonics. The generation of harmonics in subwavelength volumes is historically associated with the enhancement of electric fields in the interface of plasmonic structures. Recently, new platforms based on high-index dielectric nanoparticles have emerged as promising alternatives to plasmonic structures for many applications. By exploiting optically induced electric and magnetic response via multipolar Mie resonances, dielectric nanoelements may lead to innovative opportunities in nanoscale nonlinear optics. Dielectric optical nanoantennas enlarge the volume of light–matter interaction with respect to their plasmonic counterpart, since the electromagnetic field can penetrate such materials, and therefore producing a high throughput of the generated harmonics. In this review, we first recap recent developments obtained in high refractive index structures, which mainly concern nonlinear second order effects. Moreover, we discuss configurations of dielectric nano-devices where reconfigurable nonlinear behavior is achieved. The main focus of this work concerns efficient Sum Frequency Generation in dielectric nano-platforms. The reported results may serve as a reference for the development of new nonlinear devices for nanophotonic applications. GRAPHICAL ABSTRACT: uf0001